Habilidades especializadas do tênis: um estudo de intervenção na iniciação esportiva com crianças escolares - Píffero, Constance Muller (2010)
The purpose of the present study, with a quasi-experimental and correlational design, was to verify the influence of a Beginning Tennis Program (BTP) with two approaches - the Classical approach (CA) and the Mastery Motivational Climate approach (MA) - on the development of specialized tennis motor skills (STMS) and the associations between the specialized skills and fundamental skills. The participantes were 61 children (29 girls and 32 boys), aged 6-12 yr. (M = 9.4). Thirty children were submitted to the CA and 31 to the MA. The children were assessed using the Test of Gross Motor Development-2 (TGMD-2) and the Specialized Tennis Motor Skills instrument. The BTP was carried out in 26 weeks and implemented for MA the assumptions of the TARGET structure and the Sport Education Model, and for CA the classical models for tennis learning. Results indicated that 1) all children showed positive and significant changes (p < 0.01) in STMS; 2) there was a non significant interaction of age group (p = 0.519) and gender (p = 0.24) on STMS; 3) a restrict association in the post test between locomotor skills and specialized skills for the Mastery group. The implementation of a Beginning Tennis Program based on effective methodological proposals that are suitable for the participants' real needs fosters motor gains that reinforce children development